Assessment of Adverse Drug Events, Their Risk Factors, and Management Among Patients Treated for Multidrug-Resistant TB: A Prospective Cohort Study From Pakistan - Khan, Farman Ullah; Khan, Amjad; Khan, Faiz Ullah; Hayat, Khezar; Rehman, Asim ur.; Chang, Jie; Khalid, Waseem; Noor, Sidra; Khan, Asad; Fang, Yu (Frontiers in Pharmacology, 2022)
Background: Multidrug-resistant tuberculosis (MDR-TB) is a growing public health problem. Treatment regimens used against MDR TB are costly, prolonged and associated with more side effects as compared with the drug-susceptible. This study was framed to determine the incidence of adverse drug events, risk factors and their management in MDR-TB patients. Methods: This prospective follow-up cohort study was conducted at the site of programmatic management of drug-resistant TB located at the Pakistan Institute of Medical Sciences, Islamabad. All patients, irrespective of their age, gender, and ethnicity were included in the study. Adverse drug events were observed in patients at different time points during the study. Patients enrolled for the treatment from January 2018 were prospectively followed till December 2020 up to their end treatment outcomes. Results: Out of 126 MDR-TB patients enrolled for treatment, 116 met the inclusion criteria and were included in the final analysis. Most patients (50.9%) were between 18 and 45 years of age. A minimum of one adverse event was experienced by (50.9%) patients. Of all the adverse events, gastrointestinal disorders were more frequent (47.4 %), followed by arthralgia (28.4%) and psychiatric disturbance (20.6%). Furthermore, multivariate analysis showed a significant association with the incidence of adverse events in patients with age group above 60 years (odds ratio (OR) 4.50; 95% CI 1.05- 19.2), active smokers (OR 4.20; 95% CI 1.31- 13.4), delay reported to TB center (OR 4.03; 95% CI 1.34- 12.1) and treatment without bedaquiline regime (OR 3.54; 95% CI 1.23-10.1). Most of the patients (94.6%) counseled by the pharmacist, were found happy with the information provided by the pharmacist, and looked for more pharmacist counseling opportunities in the management of MDR-TB. Conclusions: Current findings recommend that ADEs might be well managed by timely identification and reporting. Bedaquiline coupled with other active medications lowered the chance of ADEs in MDR TB patients. Elderly patients, active smoking behaviour and those who have a delay in the treatment initiation are more prone to ADEs. Clinical Pharmacist's contribution to TB control programs may help caregivers and patients concerning the rational use of medication, early detection, and management of ADEs.